2018
DOI: 10.2147/ijn.s154325
|View full text |Cite
|
Sign up to set email alerts
|

Polymeric micelles for potentiated antiulcer and anticancer activities of naringin

Abstract: Naringin is one of the most interesting phytopharmaceuticals that has been widely investigated for various biological actions. Yet, its low water solubility, limited permeability, and suboptimal bioavailability limited its use. Therefore, in this study, polymeric micelles of naringin based on pluronic F68 (PF68) were developed, fully characterized, and optimized. The optimized formula was investigated regarding in vitro release, storage stability, and in vitro cytotoxicity vs different cell lines. Also, cytopr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 78 publications
1
41
0
1
Order By: Relevance
“…Swelling of tablets coated with EUD-L combined with 5% and 10% w/w of each release retardant was studied according to the method previously adopted. 30,31 Swelling studies were carried out to screen the effects of the natural release retardant and concentration as well as the release medium pH on the coat swelling; hence, the drug release at the three media was used.…”
Section: Swelling Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…Swelling of tablets coated with EUD-L combined with 5% and 10% w/w of each release retardant was studied according to the method previously adopted. 30,31 Swelling studies were carried out to screen the effects of the natural release retardant and concentration as well as the release medium pH on the coat swelling; hence, the drug release at the three media was used.…”
Section: Swelling Studiesmentioning
confidence: 99%
“…Slides were prepared using the manual immunohistochemistry stainer following the previously reported procedure. 49,50 Sections were deparaffinized with graded xylene and dehydrated in ethanol. Antigen retrieval was accomplished using citrate buffer pH 6.0.…”
Section: Immunohistochemical Localization Of Tnf-αmentioning
confidence: 99%
See 2 more Smart Citations
“…us, alcohol is commonly used to induce experimental gastric ulcer models in animals [9]. Most of the existing antiulcer drugs mainly work via the manner of acid suppression and indirectly promote the self-healing of gastric mucosa, but show limited efficacy [10]. Lots of clinical and experimental studies have demonstrated that utilization of herbal medicines could be a valuable alternative to cure the gastric ulcer with few adverse effects [11].…”
Section: Introductionmentioning
confidence: 99%